Landscape fire PM2.5 and hospital admissions for cause-specific cardiovascular disease in urban China - Yaohua Tian; Yudiyang Ma; Rongbin Xu; Yao Wu; Shanshan Li; Yonghua Hu; Yuming Guo (Nature Communications)
Abstract There is a growing interest in the health impacts of PM2.5 originating from landscape fires. We conducted a time-series study to investigate the association between daily exposure to landscape fire PM2.5 and hospital admissions for cardiovascular events in 184 major Chinese cities. We developed a machine learning model combining outputs from chemical transport models, meteorological information and observed air pollution data to determine daily concentrations of landscape fire PM2.5. Furthermore, we fitted quasi-Poisson regression to evaluate the link between landscape fire PM2.5 concentrations and cardiovascular hospitalizations in each city, and conducted random-effects meta-analysis to pool the city-specific estimates. Here we show that, on a national scale, a rise of 1-μg/m3 in landscape fire PM2.5 concentrations is positively related to a same-day 0.16% (95% confidence interval: 0.01%–0.32%) increase in hospital admissions for cardiovascular disease, 0.28% (0.12%–0.44%) for ischemic heart disease, and 0.25% (0.02%–0.47%) for ischemic stroke. The associations remain significant even after adjusting for other sources of PM2.5. Our findings indicate that transient elevation in landscape fire PM2.5 levels may increase risk of cardiovascular diseases.